The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1365-2427.2003.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate traits for the biomonitoring of large European rivers: an initial assessment of alternative metrics

Abstract: Summary 1. The application of environmental policy and legislation across large‐scale administrative units creates a growing need for standard tools to assess and monitor the ‘ecological health’ of rivers, a requirement that can be achieved through the description of ecological functions of lotic invertebrate species in river communities. 2. To assess alternative metrics, we tested how the functional structure (described by 14 biological traits) of invertebrate communities in 190 large river reaches differed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
200
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(211 citation statements)
references
References 61 publications
4
200
1
6
Order By: Relevance
“…Charvet et al (2000), Usseglio-Polatera et al (2000), and Gayraud et al (2003) indicate the enhanced usefulness of functional diversity in the biological assessment of different European watercourses when compared with other measures of diversity of benthic animals. Roque et al (2014) found noticeable differences between traditional diversity measures and distinctness in prediction abilities to different environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Charvet et al (2000), Usseglio-Polatera et al (2000), and Gayraud et al (2003) indicate the enhanced usefulness of functional diversity in the biological assessment of different European watercourses when compared with other measures of diversity of benthic animals. Roque et al (2014) found noticeable differences between traditional diversity measures and distinctness in prediction abilities to different environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Among the c. 600 large river species of Europe, 76% had a complete and 18% an incomplete description of the 14 traits indicated in Table 1; the traits of 6% of the species (typically rare ones) could not be described (Gayraud et al, 2003). Because species-level information was so incomplete in the North American database, Vieira et al (2006) provided data on the availability of trait information for genera.…”
Section: Technical Frameworkmentioning
confidence: 99%
“…For each m aero invertebrate species, we documented 55 categories (modalities) of 15 biological traits in a similar manner to Usseglio-Polatera et al (2000) and Gayraud et al (2003). The selected traits reflected the life history of organisms, the resilience or resistance potential beyond that of life history traits, and general biological and physiological features (see Dolédec et al 2006).…”
Section: Species Traits Analysesmentioning
confidence: 99%
“…Key life history, physiological and behavioural characteristics of stream invertebrates (or species traits) can be used to describe the functional structure of a stream community, based on taxa abundances and an array of biological traits describing size, reproductive characteristics, mobility, body form, and feeding habits (Charvet et al 1998(Charvet et al , 2000Gayraud et al 2003). Analysis of community responses to disturbance based on species traits offers an alternative or complementary approach to community structure for assessing disturbance responses in stream communities (Corkum & Ciborowski 1988;Poff & Allan 1995;Poff 1997;Lamouroux et al 2002;Dolédec et al 2006).…”
Section: Introductionmentioning
confidence: 99%